Connecting Ruthenium Photocatalysis to 1,2-Dioxetane-Mediated Chemiluminescence: a Versatile Combination for Optical Detection and Read-Out - Köckenberger, Johannes; Thurston, Ryan; Sauer, Caroline; Oppl, Janina; Heinrich, Markus (Angewandte Chemie International Edition, 2023)
Optical storage and photon quantification systems based on sensitive photoreactions have numerous applications. Herein, we report a highly efficient photocatalytic reaction, in which ruthenium photoredox catalysis is combined with a 1,2-dioxetane from which chemiluminescence can be triggered. In this system, blue light irradiation as optical input enables a defined inverse correlation with base-triggered, blue light emission as optical output. Comparison of readout by 1H NMR and chemiluminescence, relative to previous optical input, underlines the reliability and usefulness of the ruthenium-dioxetane system for optical storage, sensing and ruthenium detection.
CRIS-Team Scopus Importer:2023-07-07
Keywords: 1; 2-Dioxetanes; Actinometry; CIEEL; Optical Storage; Photocatalysis